Anatomy and Physiology of Animal Model Rats in Biomedical Research - Rachmat Hidayat; Patricia Wulandari (Fakultas Kedokteran Universitas Sriwijaya, 2021)
A distinguishing feature of rodents, including rats, is the absence of canines and the presence of prominent incisors. Rats are monophydontic, meaning they grow one set of teeth in their lifetime. The enamel of the rodent incisor contains iron, which gives it its yellow-orange color. Rats are mammals and as such, possess many similarities with other mammals. Only the peculiarities of the rat’s anatomy are addressed. Male rats reach puberty at 40 - 60 days of age. Descent of the testes usually occurs between days 30 - 60. Sperm counts vary by strain. The male rat has an os penis. Male rats have the following accessory sexual organs: ampulla, seminal vesicles, prostate, bulbourethral glands, coagulating glands, and preputial glands. The coagulating gland and prostatic and vesicular secretions are responsible for the copulation plug, a firm plug deposited in the vagina of the female after copulation. (This plug, when found outside the female rat, is capsuleshaped and approximately 5 mm long.) The male rat has no nipples. The adult male rat has a prominent scrotum and a longer anogenital distance than the female rat.